Semantics of the word (light) in the Holy Quran and the books of faces and isotopes (Journal of the College of Basic Education, 2022)
Praise be to God, the best of everything He created, good and blessed praise, as it should be for the majesty of His honorable face and His great authority.And praise be to God, a praise that no one is able to count except Him, and prayers and peace be upon the master of the Messengers Muhammad and his chosen family and companions, and after..Our pioneers are hopes since the beginning of our studies that we will continue what we have embarked on in terms of specialization, so that our research will be within the scope of Quranic studies.